Rozwiąż równania:
a) (3x - 2) (x + 1) = 3x do potęgi {2} - 5
b) (4 - 5x) ( 2 + x) = -(4 + 5x do potęgi {2})
c) 4x do potęgi {2} - 2x = (2x + 1) ( 2x - 3)
d) 3x ( 2x + 5) = (x + 3) ( 6x + 1)
proszę na dzisiaj. ;)


Odpowiedź :

Odpowiedź:

[tex]a)\\\\(3x-2)(x+1)=3x^2-5\\\\3x^2+3x-2x-2=3x^2-5\\\\3x^2+x-3x^2=-5+2\\\\x=-3\\\\\\b)\\\\(4-5x)(2+x)=-(4+5x^2)\\\\8+4x-10x-5x^2=-4-5x^2\\\\-6x-5x^2+5x^2=-4-8\\\\-6x=-12\ \ /:(-6)\\\\x=2\\\\\\c)\\\\4x^2-2x=(2x+1)(2x-3)\\\\4x^2-2x=4x^2-6x+2x-3\\\\4x^2-2x=4x^2-4x-3\\\\4x^2-2x-4x^2+4x=-3\\\\2x=-3\ \ /:2\\\\x=-\frac{3}{2}\\\\x=-1\frac{1}{2}[/tex]

[tex]d)\\\\3x(2x+5)=(x+3)(6x+1)\\\\6x^2+15x=6x^2+x+18x+3\\\\6x^2+15x=6x^2+19x+3\\\\6x^2+15x-6x^2-19x=3\\\\-4x=3\ \ /:(-4)\\\\x=-\frac{3}{4}[/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

Zobacz obrazek Beatka47